Pertanggungjawaban Pidana Penggunaan Merek Sama Dengan Merek Terdaftar Milik Pihak Lain Yang Diproduksi Dan/Atau Diperdagangkan - Muharam, Novi Asih (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
A criminal act without the right to use a brand that is completely the same as a registered mark belonging to another party for similar goods produced and/or traded as was done by Kiswantoro Bin Ahmad Muhardi in Decision Number 50/Pid.Sus/2023/PN.Tjk. The problem in this research is the factors that cause perpetrators to commit criminal acts without the right to use the same mark in its entirety as a registered mark belonging to another party for similar goods produced and/or traded based on Decision Number 50/Pid.Sus/2023/PN.Tjk. The research method uses a normative and empirical approach. The research results show that the factors causing the perpetrator to commit a criminal act without the right to use the same mark in its entirety as the registered mark belonging to another party for similar goods produced and/or traded based on Decision Number 50/Pid.Sus/2023/PN.Tjk include factors internal and external factors. Responsibility for perpetrators of criminal acts based on Decision Number 50/Pid.Sus/2023/PN.Tjk is in the form of imprisonment for 2 (two) years and a fine of IDR 10,000,000.00 (ten million rupiah)